2017
DOI: 10.1007/s10661-017-6174-1
|View full text |Cite
|
Sign up to set email alerts
|

The application of high temporal resolution data in river catchment modelling and management strategies

Abstract: Modelling changes in river water quality, and by extension developing river management strategies, has historically been reliant on empirical data collected at relatively low temporal resolutions. With access to data collected at higher temporal resolutions, this study investigated how these new dataset types could be employed to assess the precision and accuracy of two phosphorus (P) load apportionment models (LAMs) developed on lower resolution empirical data. Predictions were made of point and diffuse sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…One commonly used method for source identification is statistical analysis of water quality time series. In particular, load apportionment models (LAMs) based on concentration -discharge (C-Q) relationships (Bowes et al, 2008(Bowes et al, , 2014(Bowes et al, , 2015Greene et al, 2011;Lamba et al, 2015;Crockford et al, 2017;Glendell et al, 2018) or the identification of periods of the year when one source is believed to dominate over other sources, a method is used to disentangle point sources from diffuse sources (Legeay et al, 2015). Equations in LAMs all rely on the assumption that point source emissions are constant in time (leading to negative C-Q relationships due to dilution when discharge increases) while diffuse source emissions increase with discharge (leading to positive C-Q relationships due to mobilization and delivery of P during storm events).…”
Section: Ambiguities In the Interpretation Of River P Dynamics For Idmentioning
confidence: 99%
“…One commonly used method for source identification is statistical analysis of water quality time series. In particular, load apportionment models (LAMs) based on concentration -discharge (C-Q) relationships (Bowes et al, 2008(Bowes et al, , 2014(Bowes et al, , 2015Greene et al, 2011;Lamba et al, 2015;Crockford et al, 2017;Glendell et al, 2018) or the identification of periods of the year when one source is believed to dominate over other sources, a method is used to disentangle point sources from diffuse sources (Legeay et al, 2015). Equations in LAMs all rely on the assumption that point source emissions are constant in time (leading to negative C-Q relationships due to dilution when discharge increases) while diffuse source emissions increase with discharge (leading to positive C-Q relationships due to mobilization and delivery of P during storm events).…”
Section: Ambiguities In the Interpretation Of River P Dynamics For Idmentioning
confidence: 99%
“…Therefore, it would not be reasonable to split the 22 years into more than two periods to apply the LAM, as these models are very sensitive to the monitoring frequency and/or duration (Crockford et al, 2017). More interestingly, the estimated virtual contribution of point sources increased in the three sub-catchments.…”
Section: C-q and C-c Relationshipsmentioning
confidence: 99%
“…Despite initial studies asserting their accuracy (Bowes et al, 2008;Bowes et al, 2009;Bowes et al, 2010;Greene et al, 2011), Crockford et al (2017) found both LAMs (BM and GM) are prone to substantial errors by calculating certainty statistics for each model under varying sampling temporal frequencies. The authors concluded this having used high frequency data from a river in Ireland and the statistical method of bootstrapping (Efron, 1979) to enable the calculation of standard errors (SEs) when the LAMs were applied to Q-P datasets.…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, in point source dominated rivers P concentration should decrease as a function of Q, due to dilution, whereas the opposite would be true for diffuse pollution. Details of model functions and dissimilarities are available in Crockford et al (2017).…”
Section: Introductionmentioning
confidence: 99%